Effectiveness of Habit Reversal and Contingency Management Techniques on Study Habit Behaviour of Secondary School Students - Lasisi Adekola Kamil; Adio Abdulmutalib Opeyemi (PT FORMOSA CENDEKIA GLOBAL, 2023)
The paper investigates the impact of Habit Reversal Technique (HRT) and Contingency Management (CMT) on the study habits of secondary school students, employing a quantitative research approach and secondary data sources. The results indicated that HRT effectively improves students' study habits, while CMT also demonstrates a positive influence on study habits. The study concludes that HRT can effectively transform negative behaviors, including poor study habits, into positive ones. Additionally, CMT is found to enhance both academic and non-academic activities, including study habits. The recommendations include granting school counselors the authority to utilize HRT for treating students with inadequate study habits and implementing CMT, involving reinforcement like tokens, to motivate students to adopt positive study habits.